Efektivitas Pembelajaran Kooperatif Tipe STAD dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP Negeri 1 Labuhan Deli: Penelitian - Syafrida Hanum Hutasuhut (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In mathematics learning, students not only need to understand the concept, but also master mathematical problem-solving skills. This study aims to measure the effectiveness of the STAD cooperative learning model on students' problem-solving skills and describe the quality of the variables studied, namely the application of STAD and the mathematical problem-solving skills of students at SMP Negeri 1 Labuhan Deli. The subject of the study was the STAD model, and the object was problem-solving skills. The sample consisted of 26 students of grades VII-3. The research instruments were in the form of observation questionnaires of the learning process and problem-solving skills tests that had been validated and tested for reliability. Data were analyzed to assess the effectiveness of the learning process and the improvement of students' abilities. The results showed effective learning with an average completion rate of 75%, and there was an increase in problem-solving skills based on a comparison of pretest and posttest scores.